Un grin de jeunesse ? - Anna Dessertine (Ateliers d'Anthropologie)
Based on an ethnographic study in a Malinké village in north-east Guinea, this article considers the question of what constitutes youth in the context of rural West Africa. It examines gatherings of young men for tea, grins, to show how youth is above all relational, and that it develops in specific practices according to the interactions of individuals of one same age set (kari) with individuals of a different generation, in the village or while migrating, particularly in the region’s artisanal gold mines. It begins with an analysis of the status games that take place in grins, games in which every day, these men replay the statuses of firstborn and cadet (a child who is not firstborn), in interactions between individuals who consider themselves peers. Secondly, this article will examine the relations occasioned by these gatherings: on the one hand, with those who do not take part in them, given that these meetings take place in view of everyone in the central courtyards of residences, and on the other hand, in a context of intensification of local mobilities in the region’s artisanal gold mines.